2014
DOI: 10.1002/cne.23619
|View full text |Cite
|
Sign up to set email alerts
|

Expression of G proteins in the olfactory receptor neurons of the newt Cynops pyrrhogaster: Their unique projection into the olfactory bulbs

Abstract: We analyzed the expression of G protein α subunits and the axonal projection into the brain in the olfactory system of the semiaquatic newt Cynops pyrrhogaster by immunostaining with antibodies against Gαolf and Gαo , by in situ hybridization using probes for Gαolf , Gαo , and Gαi2 , and by neuronal tracing with DiI and DiA. The main olfactory epithelium (OE) consists of two parts, the ventral OE and dorsal OE. In the ventral OE, the Gαolf - and Gαo -expressing neurons are located in the apical and basal zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…The salamander species investigated in these previous studies commonly exhibited different binding patterns of lectins in the primary projections between the MOB and AOB. These findings suggested the involvement of glycoconjugate heterogeneity in the distinct function of the two olfactory systems, which agrees with the exclusive expression of Gαo in the AOB (Nakada et al, ). In addition, the olfactory glomeruli in the MOB are divided into a subset only in the more terrestrial salamanders (e.g.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…The salamander species investigated in these previous studies commonly exhibited different binding patterns of lectins in the primary projections between the MOB and AOB. These findings suggested the involvement of glycoconjugate heterogeneity in the distinct function of the two olfactory systems, which agrees with the exclusive expression of Gαo in the AOB (Nakada et al, ). In addition, the olfactory glomeruli in the MOB are divided into a subset only in the more terrestrial salamanders (e.g.…”
Section: Introductionsupporting
confidence: 83%
“…The distribution of olfactory G proteins has been previously reported in the olfactory organ and its primary projection of C. pyrrhogaster (Nakada et al, ). Although the MOB of C. pyrrhogaster receives exclusively axons from Gαolf‐expressing neurons, the AOB receives axons from Gαo‐expressing neurons with a small population of Gαolf‐positive axons.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This then results in the production of inositol 1,4,5-triphosphate and diacylglycerol, leading to an elevation of intracellular concentrations of Ca 2+ ([Ca 2+ ] i ) and excitation of the receptor cells17181920. We have previously observed that the neurons in the VN organ of the red-bellied newt mostly express Gα o , but that quite a few neurons express Gα olf 21. Therefore, we used a calcium imaging system to test whether imorin could increase [Ca 2+ ] i in dissociated VN cells from male newts.…”
Section: Resultsmentioning
confidence: 99%